Women and engineering, from college to the world of work (LACCEI, 2024)
From the observation, in the Delta Regional Faculty of the National Technological University, Campana town in the province of Buenos Aires, of the current and historical situation of the female shelling in the Engineering career, carrying out a theoretical analysis about the general panorama of gender inequalities in STEM (Science, Technology, Engineering and Mathematics) university careers, it is desired to determine the perception of graduates at the time of their insertion in the world of work. It is also desired to understand and document the reasons why a significantly lower number of women engineers are denoted in senior management positions, considering that there are many women in equal conditions than men, to ascend to this type of positions and who do not achieve or they can't do it. This work plans to focus on the barriers perceived by a group of women engineers graduated from the Delta Regional Faculty of the National Technological University, classifying these barriers as internal, social, interpersonal, attitudinal or interactive if they act before or after the insertion or if they are the product of the interactivity (or interaction) of combined factors at different moments of the passage through academic life.